Cord serum albumin as a predictor of neonatal hyper bilirubinemia in healthy full-term neonates - Dr. Gurdeep Singh Dhanjal; Dr. Rajesh Kumar Rathi; Dr. Sonam Agrawal; Dr. Savita (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Neonatal jaundice or icterus neonatorum is one of the common problem that is seen in newborns during first week of neonatal life. Clinical jaundice is found in about 80% of preterm and in about 60-70% of term neonates. The main objective of the study was to determine the correlation between cord serum albumin levels and development of significant hyper bilirubinemia in healthy term neonates.Methods: A prospective study was conducted on 316 healthy term neonates. Gender, mode of delivery and birth weight were taken into consideration. It was ascertained that there was no other risk factor for neonatal hyperbilirubinemia among these newborns. These neonates were divided into 3 groups, Group A (cord serum albumin levels < 2.8 gm/dl), Group B (cord serum albumin levels between 2.8 to 3.4 gm/dl) and Group C (cord serum albumin levels 3.4 gm/dl).Result: Of the 316 babies included in the study, 102 babies were under Group A, 166 babies under Group B and 48 babies under Group C. 35 babies in Group A, 5 in Group B and none in Group C developed significant hyperbilirubinemia and required phototherapy. The sensitivity and specificity of cord serum albumin level 2.8 g/dl to predict risk of development of significant neonatal hyperbilirubinemia in our study was 87.50% and 75.72% respectively.Conclusion: Cord serum albumin levels can help us to predict the possibility of significant hyperbilirubinemia among neonates. Hence this can help us to identify the at-risk neonates and utilize our limited resources efficiently among these newborns.